Differences in serum markers of oxidative stress in well controlled and poorly controlled asthma in Sri Lankan children: a pilot study - Yenuli Fernando; Pujitha Wickramasinghe; Udani De Silva; Malintha Alahakoon; K. W. D. A. Anuradha; Shiroma Handunnetti (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Background Asthma is a disease characterised by hyper responsiveness and bronchoconstriction of airways, and is a major health burden globally. A dysfunction of the oxidant-antioxidant balance, termed oxidative stress, has been implicated in the pathophysiology of asthma. The present study aims to assess the changes in oxidative stress markers, namely nitric oxide metabolites and antioxidant capacity, in children with poorly controlled and well controlled asthma, in comparison to healthy controls. Methods The present study enrolled 72 children (ages 5-15 years) classified into three groups: (1) poorly controlled asthma (n = 20), (2) well controlled asthma (n = 24) and (3) healthy controls (n = 27). An interviewer-administered questionnaire was used to record socio-demographic data of the participants. The serum concentrations of the oxidant markers (nitrite, nitrate and total nitric oxide metabolites [NOx]) were determined using the Griess test, and the total antioxidant capacity (TAOC) was determined using the ABTS decolorisation method. The concentrations of these markers were compared across the three groups. Results The three study groups were similar in terms of socio-demographic data. The differences across the three groups were statistically significant for serum concentrations of nitrate and NOx (but not nitrite) and serum TAOC. Further analyses showed that the disparity for nitrate and NOx concentrations was greatest between poorly controlled asthma and healthy controls (p = 0.001 and p < 0.001) compared to the well-controlled asthmatics and healthy controls (p = 0.036 and p = 0.049). A significant difference in serum nitrate and NOx concentrations was not observed between the two asthma groups (p = 0.311 and 0.203). The TAOC were significantly lower in poorly controlled asthmatics as compared to well-controlled asthmatics (p = 0.003) and healthy controls (p < 0.001). However, there was no significant difference in the serum TAOC between healthy controls and well-controlled asthmatics (p = 0.496). These findings may indicate that it is perhaps the higher TAOC that contributes to the well controlled state of asthma. Conclusions The present study indicated that an imbalance of oxidants and antioxidants in the serum may have an underlying role in asthma pathophysiology, and how these markers may be effective in asthma management.